Case Study of Underwater Archaeology - Ancient Dwarka, India - Rai, Satya; Jain, Veenus (International Journal of Advanced Research in Peace, Harmony and Education, 2023)
The research study deals with the aspects & methods of underwater archaeology with the help of the study of Dwarka. The method of underwater archaeology is used to locate the lost city of Lord Krishna under the water. The first underwater archaeology excavation was conducted by the Deccan College of Pune in 1979. The speed growth of the discovery of the lost city of Dwarka was done by the great archaeologist Shikaripura Ranganatha Rao (S. R. Rao) with the help of the department of the National Institute of Oceanography (NIO), Goa India. the discovery of structures of lost Dwarka was found during the excavation of Dwarka & Bet Dwarka by the unit of the National Institute of Oceanography. The archaeologist together with divers found various things like stone structures, anchors, poetry etc, the study of the lost city of Dwarka become the best place for the study of underwater archaeology in India. According to the reference to Mahabharat the city of Dwarka sunk after the death of Lord Krishna, the archaeologists try to prove the existence of this legendary city by the methods of underwater archaeology. How to cite this article: Rai S. Case Study of Underwater Archaeology - Ancient Dwarka, India. Int J Adv Res Peace Harm Edu 2023; 8(1): 1-6. DOI: https://doi.org/10.24321/2455.9326.203201